Trabalho sem futuro: a informalização na atividade dos chapas em São Paulo - Terra, Sirlei Pires (2007)
To contribute to the study on informality on the brazilian labor market, more specifically in the Municipality of São Paulo, the present thesis investigates the conditions that permeate and define the work relations of the so-called chapas, workers that load and unload trucks. The guiding field research hypotheses on which this study is based are: a) the informality of the chapa s work results from a blend of structural and circumstantial factors, respectively both the low brazilian economic performance and the ongoing company reorganization process that has taken place in the last few years; b) work conditions for chapas are all negatives; c) those workers reduce transport costs of goods and are, therefore, strategically important for carriers and their customers. A total of twelve interviews were recorded within a non-measurable universe based on a previously defined schedule, supplying the data that were analyzed to support the research. Thus, since this is an analysis of the work conditions of a single segment of activity of the informal labor market of the Municipality of São Paulo, the result is a case study. In addition to that, and since no other research of this kind was found at studying the specific references, this research can be considered unique and novel in its kind. By analyzing the literature on informality and the economic development, the results of both these factors on the working world, and the field research data, one believes to have met the objective of the present thesis: to contribute to the understanding of the informal work of the chapas especially in the city of São Paulo by helping them to express themselves and by describing their precarious working conditions that deprive them of the full practice of citizenship